TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PEMBUNUHAN BERENCANA DALAM KASUS PEMBUNUHAN BRIGADIR NOFRIANSYAH YOSUA HUTABARAT OLEH FERDY SAMBO, S.H., S.I.K., M.H : Studi Kasus Putusan Pengadilan Negeri Jakarta Selatan No. 796/Pid.B/2022/Pn Jkt.Sel - Putra, Irwan Sapta (LPPM Universitas Bina Bangsa, 2023)
This study discusses problems related to the crime of premeditated murder committed by the former Head of the Propam Polri Inspector General Pol. Ferdy Sambo, S.H., S.I.K., M.H against his own adjutant Brigadier Nofriansyah Yosua at the Police Service's house. The purpose of this research is to find out 1. What is the motive of the perpetrators of the premeditated murder? 2. What are the criminal sanctions imposed on the perpetrators of the crime of premeditated murder? This research method is normative legal research, with a case study approach based on the decision of the South Jakarta District Court No. 796/Pid.B/2022/PN JKT.SEL. Sources of data in this study using Primary, Secondary and Tertiary data sources. Normative juridical analysis. Research Results 1. The perpetrator's motive for premeditated murder of the victim was based on the story of the perpetrator's wife named Putri Candrawathi who claimed to have been abused by the victim in Magelang, which made the perpetrator angry and killed the victim by shooting the victim with a firearm. 2. The defendant Ferdy Sambo, S.H., S.I.K., M.H., in court has been proven legally and convincingly guilty of committing the crime of